CURRENT STATE OF EVALUATION ACTIVITIES AND DIRECTIONS OF ITS DEVELOPMENT IN THE WORLD AND IN UKRAINE - Grinchuk, Alisa (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2025)
Purpose: to determine the essence and content of changes in the evaluation system in the world and to make separate proposals for the development of the activities of evaluation companies, taking into account trends and areas of research. Research methods: system analysis and synthesis, methods of dialectical and formal logic, comparative and modeling allowed us to formulate and clarify the main directions of restructuring the evaluation system, changing the forms and methods of evaluation activities in modern conditions. Results: problems of further development of evaluation activities in the world and in Ukraine were identified. A number of directions were formed that can be leading in the evaluation system and influence evaluation activities as a whole. The use of computer technology and new technologies in the field of evaluation activities was analyzed. It was proved that modern evaluation activities are practically transformed into conducting relevant examinations, which requires changing the forms and methods of evaluation activities in general and involving individual specialists who can prepare examinations. In addition, it was determined that modern forms and methods of evaluation activities in the vast majority already include forecasting the development of the specified activity, which also requires the involvement of relevant specialists in conducting evaluation activities. It is separately determined that the latest automated technologies and artificial intelligence are already used in valuation activities today. Discussion: the position is argued that there are currently a number of unsettled issues in the valuation system that require the adoption of new regulatory documents. It is proposed to carry out various measures to restructure the activities of appraisers and attract new specialists to conduct relevant examinations and prepare forecasts.